THE IMPORTANCE OF PHYSIOTHERAPY AND MASSAGE IN NURSING PRACTICE - Vokhidova Feruza Ganievna; Radjabova Markhabo Botirovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Physiotherapy  and  massage  are  integral  components  of  holistic healthcare, promoting recovery, managing pain, and enhancing physical and mental well-being.  In  nursing  practice,  understanding  these  modalities  enables  nurses  to collaborate  effectively  with  physiotherapists,  guide  patients  in  rehabilitation,  and provide supportive care. This article explores the significance of physiotherapy and massage in nursing, emphasizing their roles in improving patient outcomes and overall quality of life.